Mendidik dengan pengertian: Memahami perkembangan anak untuk meningkatkan kualitas pendidikan - Lailiyah, Adhimah (Maliki Interdisciplinary Journal, 2024)
Education is the key to the nation’s progressHaving a deep comprehension while teaching is crucial for enhancing the quality of education. Educators need to understand the stages of child development, both from physical, cognitive, social and emotional aspects. This study utilizes qualitative methodologies along with reviewing literature to examine factors contributing to variations among children, tips for educating children with understanding, and the importance of self-knowledge programs for children. Factors that cause differences in children are heredity and environment. Tips for educating children with understanding are recognizing the child’s temperament, observing the child during the learning process, two-way communication, and involving the child in a self-knowledge program. Self-knowledge programs are important to help children understand their potential, not only their personality, but also their talents and interests.